Misuse of Antibiotics in Dental Practices - Meral Fatima, Lubna Yousaf, Muhammad Asif Shahzad, Faisal Liaquat, Ghulam Mohammad Paracha, Muhammad Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Since Mid 1990s dentistry based Antimicrobial prescription has emerged as the potential drive of Global phenomenon of Antibiotic resistance. However, an inappropriate prescription would not provide sufficient benefit yet it runs the risk of causing side effects. Thus prescribing Antibiotic drugs are dictated by defined criteria which all the dentists are urged to follow and practice to minimize the occurrence of resistance in individuals. The aim of this study was to assessment of the frequency of Prescribing Antibiotics by Dental Practitioners and its misuse leading to antibiotics resistance. Methodology: In this descriptive study, questionnaire based form was distributed among 250 dental practitioners and data was analyzed by using statistical Package for social learning(SPSS). Results: Amoxicillin is considered as most frequently prescribed drug (72.2%) followed by metronidazole and about 89.1% dentists are aware of the misuse of antibiotics and its emerging resistance in individuals. Conclusion: According to our survey most preferred Antibiotic used by Dental practitioners is Amoxicillin for orodental infections followed by Metronidazole. Surprisingly, most of the dentists agreed for training of Health Professionals to curtail the errors and prevention of emerging resistance.